Antimicrobial Effects of Dexmedetomidine and Midazolam in Bicarbonate Buffer: An in vitro Study - Kocatürk, Özlem; Dönmez Özkan, Hicran; Poyrazoğlu Çoban, Esin; Bıyık, Halil (Cerrahpaşa Medical Journal, 2019)
Objective: Dexmedetomidine and midazolam are commonly used sedatives, administered by infusion. The antibacterial properties of midazolam have been previously described. The aim of this in vitro study was to investigate the antimicrobial effects of dexmedetomidine, midazolam, and their solutions buffered with bicarbonate. Methods: Using the disk diffusion and broth microdilution methods, antimicrobial efficacy was tested against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Enterococcus faecalis (E. faecalis), Klebsiella pneumoniae (K. pneumoniae), Pseudomonas aeruginosa (P. aeruginosa), Staphylococcus epidermidis, Candida albicans, and Candida utilis. Results: Dexmedetomidine showed an inhibitory effect on S. aureus, E. coli, E. faecalis, and P. aeruginosa at concentrations of ≥64 µg/mL and above. The antimicrobial effect of midazolam on S. aureus, E. coli, E. faecalis, K. pneumoniae, and P. aeruginosa was observed at concentrations ≥128 mg/mL. We further noted that the antimicrobial potency of dexmedetomidine increased with the addition of bicarbonate; however, this was not observed with midazolam. Conclusion: We found that adding bicarbonate to dexmedetomidine may be beneficial in preventing bacterial contamination, especially when treating patients in intensive care. Similar to midazolam, dexmedetomidine showed antimicrobial properties against a subset of infectious microorganisms frequently encountered in a hospital environment. Our experiments indicate that the concentration-dependent antimicrobial efficacy of dexmedetomidine can be further enhanced by buffering with bicarbonate. Cite this article as: Kocatürk Ö, Dönmez Özkan H, Poyrazoğlu Çoban E, Bıyık H. Antimicrobial Effects of Dexmedetomidine and Midazolam in Bicarbonate Buffer: An in vitro Study. Cerrahpasa Med J 2019; 43(3): 69-74.